Use of First Line AEDS For the Control of Acute Seizures in Pediatric Emergency DepartmentAn Experience of Tertiary Care Hospital - Bano, Sanam; Chand, Prem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the use of first line drugs after the use of Diazepam for the control of seizures in children presenting to Pediatric Emergency Department. Study Design: Cross-sectional study. Place and Duration of Study: Pediatric Emergency Department, Aga Khan University Hospital, Karachi, from Jan to Dec 2018. Methodology: All the patients from one month to 18 years of age who presented with the seizures at the Pediatric Emergency Department were included in the study. Patients with intractable epilepsy, taking multiple anti-epileptic drugs, patients on ketogenic diet and metabolic seizures were excluded. Demographic information along with the duration of seizure, type of seizure, use of anti-epileptic drugs (AEDs) and response in the form of cessation of seizure to anti-epileptic drugs were recorded. Results: A total of 105 patients with seizures were included in this study. Mean age of the patients was 73.87 ± 54.7 months. Generalized seizures were observed in 78 (74.3%) patients. In 48 (45.7%) patients, seizures were <5 minutes of duration, while 65 (62%) patients were diagnosed cases of epilepsy. Loading dose of Levetiracetam 20 mg/kg was used as first line AED in 66 (62.9%) patients. Out of 66 patients who were given Levetiracetam, 41 (39%) did not require second drug. Conclusion: Levetiracetam was the most commonly used first line long-acting drug at our institute in all the seizure types and controlled seizures in two-thirds of the patients.